The Influence of Perceptions of MSME Entrepreneurs, Accounting Understanding and Socialization of SAK EMKM on the Application of SAK EMKM - Hidayat, Taufik; Sjarif, Devyanthi; Kusumawardani, Astrin; Pratama, Muhamad Rizki (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research combines various previous research instruments with the aim of obtaining the best results in knowing the extent of the influence of the perceptions of MSME entrepreneurs, accounting understanding and socialization of sak emkm on the application of sak emkm in the bojongsoang area In this research, quantitative techniques with descriptive and verification approaches are used to investigate the relationship between three independent variables and one dependent variable. The data for the study were separated into two categories: primary data from respondent questionnaires and secondary data from books, papers, and other relevant literature. Slovin's formula is used in determining the minimum sample size of a limited population, as well as avoiding sampling errors that may occur. In this instance, the sample was chosen using a purposive sampling strategy in conjunction with a non-probability sampling technique. 141 MSME entrepreneurs in Bojongloa Kidul sub-district were selected from a total population of 1,641 MSME entrepreneurs utilizing a purposive sampling strategy and non-probability sampling method. These entrepreneurs have met the criteria of implementing SAK EMKM which is considered to represent the entire population The results show that the way MSME entrepreneurs perceive SAK EMKM, their accounting knowledge, and their familiarity with SAK EMKM through socialization greatly affect their ability to implement it well. Therefore, efforts to improve the application of SAK EMKM should concentrate on improving MSME entrepreneurs' understanding and awareness of the accounting principles and specific requirements of SAK EMKM